Development of Novel Thin Polycaprolactone (PCL)/Clay Nanocomposite Films with Antimicrobial Activity Promoted by the Study of Mechanical, Thermal, and Surface Properties - Holešová, Sylva; Čech Barabaszová, Karla; Hundáková, Marianna; Ščuková, Michaela; Hrabovská, Kamila; Joszko, Kamil; Antonowicz, Magdalena; Gzik-Zroska, Bożena (Polymers, 2021)
Infection with pathogenic microorganisms is of great concern in many areas, especially in healthcare, but also in food packaging and storage, or in water purification systems. Antimicrobial polymer nanocomposites have gained great popularity in these areas. Therefore, this study focused on new approaches to develop thin antimicrobial films based on biodegradable polycaprolactone (PCL) with clay mineral natural vermiculite as a carrier for antimicrobial compounds, where the active organic antimicrobial component is antifungal ciclopirox olamine (CPX). For possible synergistic effects, a sample in combination with the inorganic antimicrobial active ingredient zinc oxide was also prepared. The structures of all the prepared samples were studied by X-ray diffraction, FTIR analysis and, predominantly, by SEM. The very different structure properties of the prepared nanofillers had a fundamental influence on the final structural arrangement of thin PCL nanocomposite films as well as on their mechanical, thermal, and surface properties. As sample PCL/ZnOVER_CPX possessed the best results for antimicrobial activity against examined microbial strains, the synergic effect of CPX and ZnO combination on antimicrobial activity was proved, but on the other hand, its mechanical resistance was the lowest.
Keywords: thin films; antimicrobial activity; vermiculite; nanocomposites; polycaprolactone